Exploring Aceh Fault Zone for Slip Rates and Paleoseismic Trenching Potential along Sumatran Fault - Marliyani, Gayatri Indah; Hady, Aulia Kurnia; Klinger, Yann; Setianto, Agung; Helmi, Hurien; Kurniawan, Telly; Kambali, Retno Agung Prasetyo; Sugito, Zulham; Jihad, Abdi; Setiawan, Yosi; Rusdin, Andi Azhar; Rohadi, Supriyanto; Triyono, Rahmat; Karnawati, Dwikorita (Faculty of Geography, Universitas Gadjah Mada, 2024)
We conducted a study on the Aceh Fault, an active right-lateral strike-slip fault in northern Sumatra, Indonesia. Despite its seismic hazard potential, the slip characteristics of this fault are not well-understood. Using a combination of remote sensing and field methods, we mapped the distribution of displacement recorded by offset channels along the fault. Our goal is to identify evidence of past surface rupture, characterize their tectonic geomorphology setting, and assess their potentials as slip-rate and paleoseismic sites. The documented right-lateral displacements of channels and ridges from 35 observation points are mostly in the order of magnitude of hundreds of meters, with only a few sites exhibiting meter-scale measurable offsets. Our results provide important first-order data that can be used to locate sites suitable for paleoseismic trenching or offset investigations. This information will support the development of a maximum magnitude and earthquake recurrence model of the fault, which are crucial for seismic hazard analysis in the region.